Family Therapy in Family Medicine - Laginha, Teresa (2007)
The author proposes a model of clinical intervention in general practice leading to a systemic therapeutic plan. Selects and describes how to use the major tools 'Systems Thinking' and 'Family Interview', common to both Family Therapy.